A review on carbonized natural green flora for solar desalination. (April 2022) - Arunkumar, T.; Lim, Hyeong Woo; Denkenberger, David; Lee, Sang Joon
Abstract: Solar desalination is one of the green energy processes to treat saline water and wastewater. Solar evaporation systems, formally solar stills, have been widely used to evaporate water to purify it. However, the evaporation rate in solar stills is typically low due to incoming energy used to heat the entire bulk water. In order to minimize the bulk heating, researchers have developed capillary flow-based, self-floatable, broadband photothermal absorbers (250–2500 nm wavelength) for fast solar evaporation. Recently, interfacial solar steam generation (ISSG) has attracted attention due to significant advantages in desalination and water treatment. In general, ISSG materials are classified into plasmonic metals, semiconductors, black carbon and polymer-based materials. The basic requirements for these photothermal materials include being self-floatable and having high solar absorption, fast water transport (capillary action) and low thermal conductivity to confine the heat locally. Some natural plant species satisfy these prerequisites and have been used as photothermal materials in solar steam generation (SSG). The present review exclusively focuses on the carbonized botanical species, including bamboo, corncob, corn-stalk, coconut-husk, carrot, fruit residues (cherry, grape, orange and apple), green algae, loofah fruit, magnolia fruit, mushroom, lotus leaf and seedpods, sugarcane, sunflower head, tofu, wheat flour and wood pieces for improving the evaporation rate and efficiency. Carbonization technique improves the solar absorption by increasing the carbon concentration. In addition, these floatable solar absorbers evaporate the water with the aid of natural microchannels. These materials not only improve the efficiency, but also have economic and environmental benefits. Highlights: Carbonized natural plants for solar steam generation were investigated. Inherent capillary channels ensure continuous water supply to the absorber. Plants have competitive performance and are more sustainable than synthetic options. Carbonized 3D-corncob absorber produced the highest amount of clean water at 12.32 L m −2 day −1 . Stability and salt accumulation are challenges in seawater desalination.